Endogenous trade, nontraded goods and real exchange rate variations - Marco A. Hernández (Banco de México, 2015)
This paper evaluates whether a macroeconomic trade model, where the decision of trade and the Balassa-Samuelson effect are endogenous, can explain recent empirical facts about the importance of nontraded goods prices in real exchange rate variations better than a standard Balassa- Samuelson model, where nontraded goods are exogenously determined. The model is modified and calibrated to an asymmetric equilibrium that allows the steady state of the model to match some of the US-Mexico relationships quite well. The results suggest an importance of nontraded goods in real exchange rate volatility closer to the empirical evidence. In addition, the model replicates the findings that nontraded prices exhibit higher volatility than the real exchange rate and that these prices are negatively correlated with traded goods prices.
Keywords: F12; F31; F41; 330; Real Exchange Rate; Endogenous Trade; Firm Heterogeneity; Firm Dynamics